2008
DOI: 10.1007/s00167-008-0534-x
|View full text |Cite
|
Sign up to set email alerts
|

A long-term clinical follow-up study after arthroscopic intra-articular Bankart repair using absorbable tacks

Abstract: The aim of the study was to perform an independent long-term evaluation after arthroscopic Bankart repair using absorbable tacks. We hypothesise that arthroscopic Bankart repair using absorbable tacks will result in stable shoulders. Eighty-one consecutive patients (84 shoulders) with symptomatic, recurrent, anterior, post-traumatic shoulder instability were included in the study. All the patients had a Bankart lesion. The age of the patients was 28 (15-62) years. The number of dislocations prior to surgery wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
1
22
0
6
Order By: Relevance
“…9,19 Concerning studies with a longer follow-up, Larrain et al 16 reported 8.3% recurrence in rugby players with traumatic anterior shoulder instability at a mean follow-up of 5.9 years. Elmlund et al 4 reported a 19% recurrence rate in a long-term clinical follow-up study after arthroscopic intra-articular Bankart repair using absorbable tacks. Marquardt et al 18 found an overall failure rate of 5.6% at a mean follow-up of 8.7 years using absorbable tacks; their results did not deteriorate over time.…”
Section: Discussionmentioning
confidence: 99%
“…9,19 Concerning studies with a longer follow-up, Larrain et al 16 reported 8.3% recurrence in rugby players with traumatic anterior shoulder instability at a mean follow-up of 5.9 years. Elmlund et al 4 reported a 19% recurrence rate in a long-term clinical follow-up study after arthroscopic intra-articular Bankart repair using absorbable tacks. Marquardt et al 18 found an overall failure rate of 5.6% at a mean follow-up of 8.7 years using absorbable tacks; their results did not deteriorate over time.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al 82 49 DSA 1 (2) 2 (4) 1 (2) 4 (8) Mohtadi et al 83 87 DS 16 ( 18) 4 ( 5) 20 ( 23) Zaffagnini et al 51 49 redislocation 6 (12) 6 (12) Elmlund et al 84 76 DS 8 (11) 6 ( 8) 6 ( 8) 14 ( 18) Carreira et al 85 85 DS 4 (6) 3 ( 4) 2 (3) 7 (10) Gigis et al 102 38 DS 4 (11) 5 ( 13) Shymon et al 103 71 redislocation event and/or the need for further surgical intervention 17 (24) *Only reported on dislocations.…”
Section: Recommendationsmentioning
confidence: 99%
“…10,35,37,40,42 In cases of more complex injuries with additional glenoid bone loss, soft tissue repairs alone have been shown to be insufficient in restoring shoulder stability, and recurrence rates of up to 40% have been reported. 10,14,35,41,42 Furthermore, previous studies showed the clinical and biomechanical importance of intact glenoid anatomy for shoulder stability. 8,22,30,41,46 Relevant bony glenoid defects were reported to be prevalent in 5% to 67% of shoulders with recurrent instability, 8,12,24,33,37,38 and therefore thought to be a major factor for failure of surgical repair.…”
mentioning
confidence: 99%